The creation of Pulesari Tourism Village involves social group interaction with local communities and self-confidence in circular economy - Amboningtyas, Dheasey; Lestari, Sinta Petri; Fatmasari, Dewi (Universitas Widya Mataram, 2024)
Pulesari Tourism Village offers several additional programs. It is a popular tourist destination because it thrives on community involvement. In addition, tourist cities are fashionable areas that attract visitors and influence their choice to visit modern tourist destinations. However, the amount of rubbish collected and the number of tourists increases. Therefore, it is essential to support environmental organizations in their efforts to keep areas tidy. To maintain the sustainability and cleanliness of tourist attractions, it is necessary to study the awareness of preserving ecological cleanliness through increasing self-confidence and social interaction regarding circular economy. This research used quantitative methodology and involved a total sample of 286 people, selected through systematic simple random sampling. The research sample objects include tourism awareness groups, youth organizations, farmer groups, farmer women's groups, and family empowerment and welfare. Purposive sampling was used to conduct research. Research data was analyzed using Multiple Linear Regression and Pearson correlation tests to determine the elements influencing social interaction and self-confidence about innovative (dependent) (independent) circular economy. Research findings show that although there is a weak correlation between social interaction and self-confidence, social interaction and self-confidence in responsible circular economy significantly impact maintaining the cleanliness of the tourist environment in the Pulesari tourist village. The conclusion explains that social interaction and confidence in circular economy are two ways to increase the number of tourist visits.